2021
DOI: 10.1007/s42844-021-00039-5
|View full text |Cite
|
Sign up to set email alerts
|

Fathers and Families: Risk and Resilience. An Introduction

Abstract: The articles in this special issue are informed by the historic changes in the twentieth century (i.e., decreasing family size, changing family roles, and youth demonstrating more independent behaviors) that propelled intensive study of fathers’ impacts on child development. The papers are conceptualized within a developmental systems framework and focused on a father’s presence rather than on his absence in the family, going beyond the study of merely father involvement. Papers reflect longitudinal and cross-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Recent research indicates that both mothering and fathering play a crucial role in children’s development (Cabrera et al, 2014). In response to this and to fill in the dearth of research on fathering, an increasing body of studies focus on understanding how fathers influence children’s development (Cabrera et al, 2018; Fitzgerald et al, 2021; Lamb & Lewis, 2004). The findings from the current study indicate that, overall, maternal hostility was the most important factor for predicting adolescent aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that both mothering and fathering play a crucial role in children’s development (Cabrera et al, 2014). In response to this and to fill in the dearth of research on fathering, an increasing body of studies focus on understanding how fathers influence children’s development (Cabrera et al, 2018; Fitzgerald et al, 2021; Lamb & Lewis, 2004). The findings from the current study indicate that, overall, maternal hostility was the most important factor for predicting adolescent aggression.…”
Section: Discussionmentioning
confidence: 99%
“…It highlights the complexity of family dynamics and suggests that when fathers demonstrate lower depressive symptoms, their positive psychological state may not only offset the negative in uence of maternal emotion dysregulation but could also actively contribute to a more resilient environment. The presence of at least one emotionally stable parent may help children develop effective coping mechanisms and resilience, which could reduce the occurrence of depressive problems (Fitzgerald et al, 2021). Essentially, a father with good mental health might compensate for a mother's emotion dysregulation by providing additional emotional security, modeling effective emotion regulation strategies, and fostering a supportive atmosphere that helps children navigate and adapt to their mother's emotional challenges (Goodman et al, 2011;Martin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A child’ mental health development depends on their parents or caregivers who serve as primary sources of support in reaching an adaptive development. Studies on the importance of parents’ mental wellbeing in the child development have showed that a poorer parents’ mental wellbeing is related to a higher mental, emotional or development disability [ 10 ]. In particular, parental stress has been associated with less effective parenting [ 11 ] and poorer adherence of children to medical treatment [ 12 ].…”
Section: Introductionmentioning
confidence: 99%